THE VALUES OF BATANG HARING AS LOCAL WISDOM IN BUILD ING THE SUSTAINABLE COMPETITIVE ADVANTAGE OF TOURISM DESTINATION IN CENTRAL KALIMANTAN - Mau, Daniel Pandu; Sukawati, Tjokorda Gde Raka (Journal of Business on Hospitality and Tourism, 2019)
As a regional tourism destination in Indonesia, Central Kalimantan has cultural richness from its sub-ethnics of Dayak (indigenous people in Kalimantan) that can be used to develop its tourism products. Therefore, through an ethnographic approach using triangulation data collection techniques, this study explored, illustrated and comprehended in-depth the culture of Central Kalimantan specifically local wisdom values. Batang Haring as a local wisdom of Dayak in Kalimantan, particularly Central Kalimantan, has culture value that is the balanced and harmonious relationship among three-dimensional: human, God, and nature implemented through rites of Kaharingan (traditional belief of Dayak). The uniqueness in implementing the values become a "spirit" that is able to “awaken” and more "revive" Central Kalimantan, specifically in tourism sector. The strongly formed "spirit" will be a basic strength of differentiation strategy to create different, unique and unimitate products as a factor of competitive advantage in its tourism products. Utilization of these values can be done through cultural practices, Dayak-Kaharingan rite activities, and the use of cultural symbols in its development. However, it needs to be applied consistently in everyday life and supported through the hospitality of its people who live spiritually and continue to uphold their culture and arts that will form a strong "spirit" and hard to find elsewhere. Thus, the tourism sector can be sustainable and will impact on strengthen economic activity, as well as improve the living standard of its community as host.